Evolutionary dynamics of Usutu virus: Worldwide dispersal patterns and transmission dynamics in Europe - Siljic, Marina; Sehovic, Rastko; Jankovic, Marko; Stamenkovic, Gorana; Loncar, Ana; Todorovic, Marija; Stanojevic, Maja; Cirkovic, Valentina (Frontiers in Microbiology, 2023)
Usutu virus (USUV) is an emerging mosquito-borne Flavivirus, with birds as the main zoonotic reservoir. Humans are accidental hosts and mostly develop mild or even asymptomatic infection, although severe complications such as encephalitis can also arise. Detailed characterization of the pathogen’s phylogenetics may offer valuable insights into prediction and prevention of potential epidemics; however, lack of uniformity and number of available USUV sequences worldwide hampers comprehensive investigation. Herein we report on new USUV isolate from Culex pipiens collected in 2019 in Serbia. The study aimed to investigate USUV spatio-temporal dispersal inter- and intra-continentally and to estimate dynamics of viral spread within Europe. The results of this research revealed two newly described intercontinental migration events of USUV from Africa to Germany in the 1970s and from Africa to the Middle East (Israel) in the late nineties. Finally, phylodynamic analysis substantiated ongoing active expansion of USUV in Europe, drawing attention to the need for upscaling USUV surveillance.